Analysis of Long Work, Work Posture and Low Back Pain Complaints in Rice Farmers - Ahmad Zulfikri; Putra Siregar; Watni Marpaung (International Archives of Medical Sciences and Public Health, 2022)
Low back pain is caused by non-ergonomic work and is a real health problem. Muscle disorders will be aggravated by certain situations such as improper sitting position, age, posture and chairs that are not ergonomic. This research is a qualitative descriptive study using a case study approach and extracting data or information through in-depth interviews and testing by conducting triangulation efforts to check data from various sources at various times. The informants consisted of 7 rice farmers, one village head, one health centre doctor, and one farmer leader. The research location is in Sei Bingai District, Langkat Regency, in February - July 2021. The results of the research on the causes of low back pain occur due to the workload and dynamic work postures of farmworkers, namely based on an assessment using the REBA method, the results obtained 85.71% received a value of 7 with a moderate risk level and a value of 10 with a high-risk level of 14.29%. It can be concluded that complaints of low back pain in rice farmers in Sei Bingai District, Langkat Regency occur due to posture and length of work.